Biliary Papillomatosis and New Ultrasound Imaging Modalities - Cui, X. W.; Ignee, A.; Braden, B.; Woenckhaus, M.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2012)
Biliary papillomatosis (BP) is a rare disorder of the biliary tract with a significant risk of malignant transformation and a high recurrence rate after operation due to the diffuse distribution of the disease. Preoperative diagnosis is difficult also by reason of the low sensitivity and specificity of conventional ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI), endoscopic retrograde cholangiography (ERC) and positron emission tomography (PET). Therefore, the introduction of new diagnostic imaging methods is of importance to improve the preoperative diagnosis of this originally as benign described disease which is reflected in the term of “benign papillomatosis of the biliary tree”. The present review summarizes the literature and discusses new sonographic imaging techniques including contrast-enhanced ultrasound (CEUS), contrast-enhanced low mechanical endoscopic ultrasound (CELMI-EUS) and endoscopic ultrasound elastography.
Keywords: biliary papillomatosis; cholangiocellular adenoma; cholangiocellular carcinoma; contrast-enhanced ultrasound; endoscopic ultrasound; elastography